Hyperphosphatemia Contributes to Inflammation and Iron Dysregulation in Models of Normal and Impaired Renal Function - Czaya, Brian; Richter, Beatrice; Yanucil, Christopher; Campos, Isaac; Heitman, Kylie; Faul, Christian (Blood, 2019)
Background Fibroblast growth factor (FGF) 23 is a phosphaturic hormone that targets the kidney to promote urinary phosphate excretion. In patients with chronic kidney disease (CKD), serum concentrations of phosphate (Pi) and FGF23 gradually increase as renal function declines and associate with various pathologies, including systemic inflammation and anemia. Our previous studies revealed FGF23 contributes to inflammation by directly targeting hepatocytes via FGF receptor 4 (FGFR4) and inducing phospholipase Cγ (PLCγ) signaling and the expression of inflammatory cytokines. Experimental studies have shown Pi can accelerate CKD-associated pathologies, but direct effects of Pi on the liver are not well described. Here we compare the effects of Pi versus FGF23 on hepatocytes and determine their respective contributions to inflammation and anemia in the context of CKD. Methods We subject mice with global deletion of FGFR4 and wild-type littermates to increasing dietary Pi load (0.7%, 2.0%, or 3.0%) or an adenine-rich diet (used as a CKD model) in order to examine systemic inflammation and alterations in iron metabolism in the setting of normal and impaired renal function. In addition, we study primary mouse hepatocytes treated with FGF23 and increasing Pi concentrations and examine the activation of downstream signaling events and expression levels of specific target genes. Furthermore, we determine if co-treatment with inhibitors of Pi uptake and downstream signal mediators block the observed effects. Results A 3% Pi diet as well as an adenine-rich diet promote inflammation and iron dysregulation in mice. These effects are exacerbated in FGFR4 knockout mice. In cultured hepatocytes, expression of inflammatory cytokines, hepcidin and FGF23 are induced by Pi in a dose-dependent manner. Furthermore, Pi activates NFkB signaling and the inhibition of Pi uptake and of NFkB protects from Pi-induced effects. Conclusion We postulate that in CKD, gradual elevations in serum Pi promote inflammation and anemia by targeting the liver to induce gene programs which regulate the inflammatory response and iron metabolism. Our study indicates these Pi effects may be independent of FGF23. Pharmacological approaches targeting hyperphosphatemia or hepatic Pi actions might alleviate various CKD-associated pathologies. No relevant conflicts of interest to declare.